Laugier–Hunziker Syndrome in an 8-Year-Old Boy with Scleral Melanocytosis, Lingual Pigmentation, Labial Pigmentation, and Melanonychia Striata - Alexander K. C. Leung; Kin Fon Leong; Benjamin Barankin; Joseph M. Lam (Case Reports in Pediatrics)
Laugier–Hunziker syndrome is a rare, acquired disorder characterized by mucocutaneous hyperpigmentation and melanonychia striata with no underlying systemic abnormalities. We report an 8-year-old boy with Laugier–Hunziker syndrome who presented with melanonychia striata affecting all the fingernails and toenails, macular pigmentation on the tongue and the lower lip, and scleral melanocytosis. Melanonychia striata rarely affect all the twenty nails, and scleral melanocytosis has rarely been reported in association with Laugier–Hunziker syndrome. Laugier–Hunziker syndrome occurs predominately in adults. Our patient is the youngest reported patient with Laugier–Hunziker syndrome.